Local firms spillovers from multinationals’ exports in Switzerland - Lamia Ben Hamida (Small Business International Review)
This paper aims to examine how local firms can learn from the export activities of large multinational corporations (MNCs). Arguing that MNCs’ export activities could act as catalysts for local firms, allowing them to start exporting or intensify their export volume, we hypothesize that the size and extent of export spillovers depend on the linkage between local firms and MNCs, the geographical distance between them in the home country, and the foreign export market destination in terms of psychic distance from the home market. Using Swiss manufacturing firm-level data, we found support to this learning by exporting effect through which local firms benefit from the presence of MNCs’ exporter counterparts and the export activities of their upstream MNCs’ suppliers, with particular effects of the nature and the physical location of destinations. From these findings, several important academic and practical implications are exhibited and discussed